A Novel Approach for Studying Pythagorean Triples Suitable for Students at all Educational Levels (European Journal of Pure and Applied Mathematics, 2024)
This paper seeks to showcase how a new approach can breathe new life into research within the traditional domain of Pythagorean triples, introducing innovative applications to invigorate the field. This serves not only as an exemplar but also as a wellspring of inspiration for students at both school and university levels. The demonstrations will underscore that, with fundamental mathematical concepts and unencumbered by intricate calculations, one can unveil novel results and applications with ease. The new results and applications, along with those found in the Preliminary Results section, show how the field of Pythagorean triples is still interesting and stimulating to study, despite the centuries that have elapsed.
Keywords: Pythagorean triples; Diophantine equations; Algebric groups; Geometry